The Effect of Number of Spark Plug Ground Electrodes and Octane Rating on Single Cylinder Engine Performance - Winoko, Yuniarto Agus; Sudarmanto, Jefri Haris (International Journal of Marine Engineering Innovation and Research, 2024)
Vehicle ignition systems, including spark plugs, are a certain way to boost a motorcycle's performance. One kind of spark plug used to ignite the combustion process in a gasoline engine is a multi electrode spark plug, which has two or more ground points built into the electrodes. This study's overarching goal is to identify the optimal combination of multi-ground spark plugs, gasoline octane value fluctuations, and power/torque/specific fuel consumption parameters. Engine performance testing relies on data collected from controlled laboratory tests. In addition, Microsoft Excel is used for data analysis, and the results are shown in graph tables. Spark plug electrode amount in feet and gasolines octane level are the independent variables. Speed the engine from 5500 to 9000. The peak power output of 6.92 Hp was achieved at 7000 rpm in the power test with RON 92 gasoline X-Line spark plugs. At 5500 rpm, the maximum torque of 8.21 Nm was produced by the torque test using RON 98 gasoline X-Line spark plugs. At 6000 rpm, the specific fuel consumption test with RON 90 fuel and standard spark plugs yields a value of 0.0800 kg/Hp.hour.